PREDIKTOR INDEPENDEN PERPANJANGAN INTERVAL QTc PADA PASIEN TUBERKULOSIS RESISTAN OBAT (TB-RO) - M. Hasan Andryanto; Soedarsono Soedarsono; Amelia Lorensia; Umi Fatmawati (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
Drug-resistant tuberculosis (DR-TB) remains a global health challenge with suboptimal treatment success rates. Long-term treatment regimens in DR-TB patients may lead to cardiotoxic adverse effects, including QTc interval prolongation, which increases the risk of fatal arrhythmias such as torsades de pointes. This study aimed to analyze the independent predictors of QTc interval prolongation in patients with DR-TB receiving long-term treatment regimens. A retrospective cohort study was conducted at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from January 2021 to December 2023. A total of 100 eligible DR-TB patients were included. QTc prolongation was defined as ≥ 450 ms in males and ≥ 470 ms in females using Bazett’s or Fridericia’s correction. Bivariate analysis was performed using the Mann–Whitney test and chi-square or Fisher’s exact. Multivariate logistic regression analysis was subsequently conducted to identify independent predictors of QTc interval prolongation. The results showed that 60% of patients experienced QTc interval prolongation. Multivariate analysis revealed that age ≥ 60 years (adjusted OR 6.94; 95% CI 1.34–35.98; p = 0.021) and diabetes mellitus (adjusted OR 8.76; 95% CI 2.99–25.68; p < 0.001) were independent predictors of QTc interval prolongation in patients with DR-TB receiving long-term treatment regimens. Diabetes mellitus was identified as the strongest independent risk factor in this study. These findings highlight the importance of cardiometabolic risk stratification and more intensive electrocardiography (ECG) monitoring in patients with these risk factors to improve treatment safety.